Two zebrafish (Danio rerio) antizymes with different expression and activities. - Saito, T (2000)
Cellular polyamines are regulated by a unique feedback mechanism involving ornithine decarboxylase (ODC) antizyme. The synthesis of mammalian antizyme requires a programmed translational frameshift event induced by polyamines. Antizyme represses ODC, a key enzyme for polyamine synthesis, through accelerating enzyme degradation by the 26 S proteasome. Antizyme also inhibits the cellular uptake of polyamines. In the present study we isolated two distinct zebrafish (Danio rerio) antizyme cDNA clones (AZS and AZL) from an embryonic library. Their sequences revealed that both clones required translational frameshifting for expression. Taking account of +1 frameshifting, AZS and AZL products were 214 and 218 residues long respectively and shared 51.8% amino acid identity. In rabbit reticulocyte lysates, both mRNA species were translated through spermidine-induced frameshifting. The presence of the two antizyme mRNA species in embryos, adult fish and a cultured cell line was confirmed by Northern blot analysis. The ratio of AZS mRNA to AZL mRNA in the adult fish was 1.8-fold higher than in the embryos. Whole-mount hybridization in situ demonstrated that both mRNA species are expressed in every tissue in embryo, but predominantly in the central nervous system and the eyes. Bacterial expression products of both cDNA species inhibited ODC activity, but only the AZS product accelerated ODC degradation in vitro. These results show that both zebrafish antizymes are induced by polyamines but their mRNA species are expressed differently during development. The difference in activities on ODC degradation suggests their functional divergence.